EXPLORING BURNOUT AND MENTAL FATIGUE AMONG HEALTHCARE WORKERS IN TOURISM-BASED CLINICS IN BALI, INDONESIA: A QUALITATIVE PHENOMENOLOGICAL STUDY - Agus Wahyu Permana; Elsye Maria Rosa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background. Burnout has become a major occupational health concern among healthcare professionals worldwide. Healthcare workers employed in tourism-oriented healthcare facilities face additional challenges compared with those in conventional healthcare settings, including multilingual communication, cross-cultural interactions, fluctuating patient volumes, emergency care for international travelers, and elevated service expectations. These unique workplace characteristics may increase the risk of emotional exhaustion and mental fatigue. Despite the rapid growth of tourism healthcare in Indonesia, qualitative evidence exploring burnout among healthcare workers in tourism-based clinics remains limited. Objective. This study aimed to explore the lived experiences of burnout and mental fatigue among healthcare workers employed in tourism-based clinics in Bali and to identify occupational, organizational, and cross-cultural factors contributing to burnout while exploring coping strategies used to maintain psychological well-being. Methods. A qualitative phenomenological study was conducted among healthcare professionals working in tourism-based clinics in Bali. Purposive sampling was used to recruit participants who had at least one year of clinical experience in tourism healthcare. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke’s six-phase thematic analysis. Credibility was enhanced through member checking, triangulation, and peer debriefing. Results. Four healthcare professionals representing nursing, midwifery, and general medical practice participated in this study. Seven interconnected themes emerged from the analysis: (1) high workload creates continuous emotional pressure; (2) emotional exhaustion as the dominant dimension of burnout; (3) mental fatigue reduces cognitive performance; (4) cross-cultural communication increases occupational stress; (5) organizational challenges contribute to burnout; (6) coping strategies improve psychological resilience; and (7) expectations toward organizational improvement. High patient volume during tourism seasons, language barriers, staff shortages, administrative burden, and limited organizational support were identified as major contributors to burnout. Participants described peer support, family support, spirituality, exercise, and work–life balance as important protective factors. Conclusion. Burnout among healthcare workers in tourism-based clinics is a multidimensional phenomenon shaped by occupational demands, cross-cultural communication challenges, organizational factors, and psychological stress. Organizational interventions focusing on workforce planning, staffing adequacy, administrative digitalization, leadership support, and employee well-being programs are essential to improve healthcare quality, patient safety, and workforce sustainability within tourism healthcare services.